The association between the severity of erectile dysfunction and left ventricular diastolic dysfunction in patients with and without cardiovascular disease - Chan Wan Hyun; Jae Young Hwang; Seong Woo Yun; Tae Young Park; Sung Goo Yoon; Seung Bin Kim; Tae Il Noh; Sung Gu Kang; Seok Ho Kang; Dong-Hyuk Cho; Ji Sung Shim (Investigative and Clinical Urology, 2024)
Purpose: Erectile dysfunction (ED) is considered a microvascular disorder and serves as an indicator for the potential development of cardiovascular disease (CVD). Although left ventricular diastolic dysfunction (LVDD) reflects early myocardial damage caused by microvascular disorders, the association between ED and LVDD remains poorly elucidated. Materials and Methods: A cross-sectional study was conducted on 123 patients with ED. They underwent RigiScan, and conventional echocardiography, and attempted International Index of Erectile Function (IIEF) questionnaire. ED severity was evaluated by measuring changes in the penile base circumference and duration of penile rigidity (≥70%) during erection. The early diastolic velocity of mitral inflow (E) and early diastolic velocity of the mitral annulus (e′) were measured using echocardiography. The patients were grouped based on the presence of CVD. Results: Among 123 patients, 29 had CVD and 94 did not. Patients with CVD exhibited more pronounced ED and more severe LVDD. Associations between increased penile circumference with echocardiographic parameters were more prominent in patients with CVD than in those without CVD (ΔTtop and e′ wave, r=0.508 and r=0.282, respectively, p for interaction=0.033; ΔTbase and E/e′ ratio, r=-0.338 and r=-0.293, respectively, p for interaction <0.001). In the multivariate linear regression, the increase of penile base circumference was an independent risk factor for LVDD (e′, B=0.503; E/e′ ratio, B=-1.416, respectively, p<0.001). Conclusions: ED severity correlated well with LV diastolic dysfunction, particularly in the presence of CVD. This study highlighted the potential role of ED assessment as early indicator of CVD development.